1995
DOI: 10.1111/j.1440-1630.1995.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy practice with clients from non‐English speaking backgrounds: A survey of clinicians in south‐west Sydney

Abstract: Australia is a multicultural society and this has important implications for the health care worker. The aim of this study was to investigate the experiences of occupational therapists who work with clients from non‐English speaking backgrounds (NESB). The ‘cross‐cultural therapy questionnaire’ was developed by the author and distributed to 65 occupational therapists employed in either the South‐Western Sydney Area Health Service or Western Sydney Area Health Service. Issues explored in this questionnaire incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Previous studies have suggested that differences in cultural models of rehabilitation between therapists and patients may influence the therapeutic relationship and lead to incompatibility of goals [9,23,24]. The current study supported these findings, but also added new information that therapists find it more difficult to negotiate and bridge these cultural perspectives when there is a language barrier.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previous studies have suggested that differences in cultural models of rehabilitation between therapists and patients may influence the therapeutic relationship and lead to incompatibility of goals [9,23,24]. The current study supported these findings, but also added new information that therapists find it more difficult to negotiate and bridge these cultural perspectives when there is a language barrier.…”
Section: Discussionsupporting
confidence: 87%
“…Engagement could conceivably become more difficult when there is a language barrier, but this does not appear to have been explored previously. Cultural attitudes have been identified as a factor in care provision and rehabilitation, and it has been noted that there may be a dissonance in cultural attitudes between therapists and clients [9,[23][24][25]. It is plausible that individuals, professionals and care-givers may be less likely to overcome cultural differences if they are not able to discuss different attitudes and approaches clearly due to a language barrier.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…One way t o begin to address this question. as Phipps (1995) pointed out. is to explore what practising therapists identify as the key issues.…”
Section: Valuesmentioning
confidence: 92%
“…The one research article specifically addressing cultural issues encountered in practice was based on 65 responses to a mailed-out questionnaire sent to therapists working in south-west Sydney (Phipps, 1995). Our paper.…”
Section: Methodsmentioning
confidence: 99%